THE IMPACT OF THE REGENT'S INSTRUCTION REGARDING IMPLEMENTING LIMITATIONS OF OPERATIONAL ACTIVITIES IN HANDLING COVID – 19 FOR THE ECONOMY OF THE COMMUNITY OF WAMENA CITY, JAYAWIJAYA REGENCY - Tati Haryati; Ahmad; Wahyu Adi Pratama (International Journal of Social Science, 2022)
The Jayawijaya Regent's instruction required the community to limit operational hours for the community. This has an impact on the economy of the people of Wamena City, who actually have not fully recovered from the post-riots and must be confronted with health problems like this. This is a serious blow to the people of Wamena City who have to live with the fear of contracting a deadly disease. This study aims to analyze the economic impact of the presence of Covid-19 because of the many complaints from economic actors who do not provide flexibility to do activities as before. Not obeying the rules will have an impact on health, but if allowed to continue, their lives will still be threatened. People asked the government to quickly tackle this problem, and hope that this disease will quickly pass. This research is a descriptive qualitative study to explain how big the impact of Covid-19 is on the economy of the people of Wamena City. The result is the emergence of unrest in society, both health problems and economic problems that cause the community to find it difficult to meet their basic needs